(untitled) (Journal of the College of Basic Education, 2022)
The research focuses on the axis of the mechanism of diversity of the actor’s performance in monodrama performances and identifying the artistic characteristics of that diversity. In the first chapter, he dealt with the research problem that focused on what are those characteristics that the actor possesses during the diversity of performance between the characters he performs, and are these characteristics related to the nature of the monodrama as a form of Forms of drama with monotherapy, the researcher defined the title of his research as (the diversity of the actor’s performance in monodrama shows) d